2006
DOI: 10.1590/s1516-35982006000400019
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do farelo de algodão, com ou sem a adição de ferro, na alimentação de leitões na fase inicial (15-30 kg)

Abstract: RESUMO -Um experimento foi conduzido para verificar os efeitos da inclusão de três níveis (0, 8 e 12%) de farelo de algodão contendo 36% de PB (FA 36 ) e três níveis (0, 20 e 40 g/100 kg de ração) de sulfato de ferro (FeSO 4 Effects of feeding cottonseed meal with or without iron addition for starting piglets (15-30 kg)ABSTRACT -A trial was carried out to evaluate the effects of increasing levels (0, 8 and 12%) of cottonseed meal 36%(CM 36 ) and three inclusion levels (0, 20, and 40 g/100 kg) of ferrous su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
2
2
1
4
Order By: Relevance
“…Moreira et al (2006) observed MCV of 56.04 fL for pigs at an early stage, which were higher when compared to the present study. MCV and Hb were below the ideal values, probably due to the age of the animals and the kind of nutritional management employed.…”
Section: Resultscontrasting
confidence: 87%
“…Moreira et al (2006) observed MCV of 56.04 fL for pigs at an early stage, which were higher when compared to the present study. MCV and Hb were below the ideal values, probably due to the age of the animals and the kind of nutritional management employed.…”
Section: Resultscontrasting
confidence: 87%
“…Prod. Anim., Salvador, v.15, n.3, p.790-800 jul./set., 2014 Os resultados da fase de crescimento foram semelhantes aos encontrados por Moreira et al (2006), os quais não observaram influência da inclusão da inclusão de FA sobre o desemenho zootécnico e NUP para leitões (15-30 kg de peso vivo) com até 12% de inclusão de farelo de algodão. Na terminação, foi verificado maior (P<0,05) consumo diário de ração (CDR) e pior conversão alimentar (CA) com a inclusão do FA42.…”
Section: Resultsunclassified
“…Como fator limitante na utilização desse coproduto na alimentação de suínos, existe o gossipol, composto que interfere no aproveitamento dos minerais, formando complexos estáveis com cátions de ferro, podendo, assim, ocasionar anemia. Uma solução para isso é a adição de sais de ferro à dieta, como sulfato ferroso, utilizado na proporção 1:1 (ferro:gossipol livre) (Moreira et al, 2006).…”
Section: Introdução unclassified